Kajian Bibliometrik Publikasi Bidang Perkebunan - Etty Andriaty (Media Pustakawan, 2022)
The plantation sector has large to the country's foreign exchange, employment provider farmers welfare and national economic growth. This study aims to find out: 1) the development of scientific, 2) distribution of affiliation, 3) distribution of scientific papers by commodity, 4) Patterns of authorship and productivity of researchers. The study uses a bibliometric approach from March to September 2022. The object of this study is scientific papers in the plantation sector. The indicators studied were: author, affiliation, commodity, authorship pattern, and productivity. The pattern of authorship is seen from single author and multiple author, as well as the level of collaboration which is calculated based on the Subramanyam formula. The results show that the number of scientific articles of plantations during the 2015-2021 period was 596 titles which were published nationally and internationally. The highest affiliation was Balittro (329), while the lowest was Puslitbangbun (108). The highest researched and published commodities were sugar cane, coconut and coffee with 66, 65 and 59 titles respectively, followed by cocoa with 46 titles and pepper with 36 titles. The most productive researchers publishing scientific articles are Edi Wardiana (21 titles), Rita Harni (17 titles) and Nurindah, M. Syakir, Ismail Maskromo and Miftahorrachman, 16 titles each. Most (89.93%) of scientific articles are written in collaboration, while the articles written by a single author are 10.07%. Based on calculations using the Subramanyam formula, the average collaboration level of plantation researchers is 0.902. This figure shows that most scientific articles on plantations are written in collaboration.